Epidemiological study on Mycobacterium tuberculosis complex and Mycobacterium avium complex in free-range and captive wildlife in Malaysia - Madaki, Lekko Yusuf (2022)
Mycobacterium tuberculosis complex (MTBC) and Mycobacterium avium complex (MAC) are the causative for chronic diseases affecting domestic animals, wildlife and humans. Globally, the role of maintenance host for MTBC and MAC is known for some wildlife species. However, the epidemiology in the local free-ranged and captive wildlife in Malaysia is still undiscovered. Therefore, the aim of this study was to get the insight of these important mycobacteria among wildlife in Malaysia by a selected antemortem and postmortem diagnostic methods namely humoral and cell mediated immunity tests, macroscopic TB-like lesions (TBLL) and antigen detection by culture and molecular. Lungs, lymphoid tissues and blood were collected from carcasses of free-ranged wild boar (n=30) and long-tailed macaque (n=42) within the wildlife-human conflict (WHC) area in Selangor. Trunk washed and blood from living captive Asian elephants (n=21) were sampled in National Elephant Conservation Centre (NECC), Pahang, and n=12 living captive non-human primates (NHPs) were collected from the zoological parks in Melaka includes blood, pharyngeal swab and comparative tuberculin palpebral skin test. Results showed that MTBC seropositive rate in wild boar was 16.7% (7.3-33.5 at 95% CI) and 10% (3.5-25.6 at 95% CI) using established an in-house ELISA bPPD and commercial DPP® VetTB kit, respectively; while for wild macaques and Asian elephant were seronegative. Wild boar gross TBLL of tonsils, submandibular LN, and lungs, spleen, kidney, liver, and mesenteric lymph nodes (LN) showed prevalence of 30% (9/30) at 95% CI. Multiple nodular lesions with necrotic-miliary and cavitation were found in submandibular LN, tonsil, lung, kidney and liver, while single nodular lesion was observed at the mediastinal LN, spleen and mesenteric LN. Conventional PCR from submandibular LN of wild boar with TBLL showed 75% (9/12) detection for M. bovis (95% CI: 46.77-91.11) and 100% were positive for MAC. In wild macaques, PCR showed 33.3% (10/30) detection for MAC and all PCR negative against MTBC. For captive NHPs, only two Orang utans (16.7%) were reacted to tuberculin test and both seropositive against MTBC, while other NHPs were seronegative. PCR from all blood and pharyngeal swabs were negative for MTBC, however all samples (100%) were PCR positive for MAC. PCR of trunk washes and blood samples in Asian elephants were 95% (20/21) and 23% (5/21) positive for MAC respectively, but all negative against MTBC. The direct use of commercial IDEXX® M. bovis ELISA kit was not able to detect antibodies against MTBC from wild boar serum samples, this could be due to the nonspecies specific of the conjugates in the ELISA kits. However, the modified protocol using both goat anti-pig IgG and Recombinant Protein-G as conjugates in the commercial kit improves MTBC detection at 5/30 (16.7%) of wild boar serum samples with 62.5% and 88.2% sensitivity and specificity respectively. The establishment of modified protocol of an in-house ELISA aPPD against MAC antibodies in primates using different conjugates namely Protein-G and anti-monkey IgG at different dilutions were able to detect at rate 25% to 100% and 16% to 100%, respectively. In conclusion, our initial studies showed a natural TB infection exists in free-ranging wild boar in Selangor and their potential as maintenance host should be further studied as it may help the understanding of TB epidemiology among livestock, wildlife and human. A significant detection of MAC among free-ranged wild macaques, captive Asian elephant and captive non-human primates indicate the important to review its control measures as it might cause health issues and may complicate the TB diagnosis. Implementing a combination of several diagnostic methods for MTBC and MAC detection and improvement of antibody rapid test would have enhanced the effectiveness of TB surveillance programs.